AN ERROR ANALYSIS OF WRITING STATUS USING RECOUNT TEXT ON SOCIAL MEDIA - Cynthia Safira Hartati; Dina Irmayanti Harahap (Journal MELT (Medium for English Language Teaching), 2021)
The resolved of this scrutiny was to ascertain ilk of errors in Writing status using Recount text on Social Media. The stamp of probe was qualitative. The array of this inspect was eighth grade students of SMP Swasta Darussalam, incorporated of 30 frosh. The dossier was obtained by affix status on social media. To scrutinize the deeds, analyzer exerted table of hold-out. The elevated dosage of errors and the stubby bulk of errors are the final denouement and reverberation. The consignment errors which are inflated are spelling with the gamut errors is 84 or 9.9%, word choice assortment errors  is 83 or 9.8%, and add a word the span errors  is 80 or 9.4%. Betoken low errors are unclear meaning with 32 errors or 3.7%, run on is 36 errors or 4.2%, and word-form is 54 errors or 6.3%.